1994
DOI: 10.1007/bf00019411
|View full text |Cite
|
Sign up to set email alerts
|

Spectral changes of the B800–850 antenna complex from Ectothiorhodospira sp. induced by detergent and salt treatment

Abstract: We have studied the effects of the detergent lauryl dimethylamine N-oxide and NaCl in the near infrared absorption spectra of the B800-850 antenna complex from Ectothiorhodospira sp. Strong spectral changes were induced on the BChl850 band by the lauryl dimethylamine N-oxide consisting of a blue shift, from 857 to 839-837 nm, and a hypochromism. No significant effects were detected on the BChl800 band in the same conditions. The changes were reversible after removing most of the detergent from the sample. Depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 34 publications
3
39
2
Order By: Relevance
“…Similar behavior was reported on the LH2 complexes from purple sulfur bacterium Ectothiorhodospira sp. (de Zarate and Picorel 1994) and purple nonsulfur bacterium Rhodovulum sulfidophilum (formerly Rhodobacter sulfidophilus) (Tadros et al 1995), where the blue shifts were observed only for the B850 band in LDAO solution, and NaCl was able to restore the spectra. Interaction between detergents and LH2 polypeptides can be confirmed from the crystal structures.…”
Section: Discussionmentioning
confidence: 96%
“…Similar behavior was reported on the LH2 complexes from purple sulfur bacterium Ectothiorhodospira sp. (de Zarate and Picorel 1994) and purple nonsulfur bacterium Rhodovulum sulfidophilum (formerly Rhodobacter sulfidophilus) (Tadros et al 1995), where the blue shifts were observed only for the B850 band in LDAO solution, and NaCl was able to restore the spectra. Interaction between detergents and LH2 polypeptides can be confirmed from the crystal structures.…”
Section: Discussionmentioning
confidence: 96%
“…As m entioned in the Introduction both LDAO (Ortiz de Zarate and Picorel, 1994) and alkaline pH (Buche and Picorel, 1998) induce a reversible blue shift of LHIIB850 from Ectothiorhodospira sp. Both treatm ents affect poorly the spectral properties of the complex in a wavelength range from the Soret band to B800.…”
Section: Resultsmentioning
confidence: 92%
“…B850 were reported (Ortiz de Zarate and Picorel, 1994;Buche and Picorel, 1998;Buche et al, 2000;Buche, 2000). The detergent LDAO generates a 19 nm blue shift of this band which was attributed to the loss of one or two H links (Ortiz de Zarate and Picorel, 1995).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations